2010
DOI: 10.1007/s00049-010-0056-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological responses of Dendroctonus armandi (Coleoptera: Curculionidae: Scolytinae) to volatiles of Chinese white pine as well as to pure enantiomers and racemates of some monoterpenes

Abstract: To better understand the attractiveness of host tree, Chinese white pines (Pinus armandi Fr.) to Chinese white pine beetle (Dendroctonus armandi Tsai and Li), the antennal responses of D. armandi to the host volatile, as well as the pure enantiomers and racemates of some monoterpenes, were examined using an electroantennogram (EAG).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…For example, ( E )-β-caryophyllene was reported to disrupt the attraction of Pityogenes bidentatus (Herbst), a small bark beetle that colonizes diseased or weakened branches of Scots pine, Pinus sylvestris L. , to its aggregation pheromone (Byres et al 2004). On the other hand, increased numbers of Dendroctonus armandi Tsai & Li, a serious pest of Chinese white pine, Pinus armandii Franch., were captured when ( E )-β-caryophyllene was present in combination with other host semiochemicals such as α-pinene (Zhang et al 2010). Other research on ( E )-β-caryophyllene showed that when this compound was produced by certain maize lines, entomopathogenic nematodes that prey on maize root herbivores, such as Heterorhabditis megidis Poinar, Jackson & Klein , were recruited (Rasmann et al 2005).…”
Section: Volatiles From Ophiostomatoid Fungi and Their Effects On Barmentioning
confidence: 99%
“…For example, ( E )-β-caryophyllene was reported to disrupt the attraction of Pityogenes bidentatus (Herbst), a small bark beetle that colonizes diseased or weakened branches of Scots pine, Pinus sylvestris L. , to its aggregation pheromone (Byres et al 2004). On the other hand, increased numbers of Dendroctonus armandi Tsai & Li, a serious pest of Chinese white pine, Pinus armandii Franch., were captured when ( E )-β-caryophyllene was present in combination with other host semiochemicals such as α-pinene (Zhang et al 2010). Other research on ( E )-β-caryophyllene showed that when this compound was produced by certain maize lines, entomopathogenic nematodes that prey on maize root herbivores, such as Heterorhabditis megidis Poinar, Jackson & Klein , were recruited (Rasmann et al 2005).…”
Section: Volatiles From Ophiostomatoid Fungi and Their Effects On Barmentioning
confidence: 99%
“…During the stimulation, air at a rate of 20 mL/min was applied through the pipette into the main airflow for 0.2 s. An interval of at least 1 min between puffs was used to ensure complete antenna recovery. A male or female antenna was tested with only one volatile . A hexane‐only control and a standard solution (1‐hexanol at 1 μg/μL in hexane) were tested before and after each test volatile.…”
Section: Methodsmentioning
confidence: 99%
“…Some volatiles ( -phellandrene, (−)--pinene, (+)--pinene, (−)--pinene, (−)-camphene, -myrcene, (S)-(−)-limonene, (+)-camphene, (R)-(+)-limonene, (+)-3-carene and -caryophyllene) from P. armandi have been detected by EAG responses. [31][32][33] Additionally, some host volatiles ( -pinene, (−)--pinene, -myrcene, (+)-3-carene, D-limonene, (+)-longifolene, (−)-camphene and -phellandrene) and non-host volatiles (cis-3-hexen-1-ol, benzaldehyde, 1-octen-3-ol, 1-hexen-3-ol, 3-octanol and trans-2-hexen-1-ol) and hindgut extracts ( -caryophyllene, -pinene, (+)-3-carene, myrcene, limonene, exobrevicomin, 1-methyl-2-cyclohexen-1-ol, seudenol, cis-verbenol, trans-verbenol and verbenone) of D. armandi have been measured in Y-tube and field trials. 4,5,26,34,35 By contrast, myrtenol, myrtanol and myrtenal have never been assessed using EAG, Y-tube or toxicity assays.…”
Section: Introductionmentioning
confidence: 99%
“…The test method used was that described by Zhang et al (2010). The antennae of D. armandi were dissected under a microscope and were connected between two electrodes.…”
Section: Eag Assaysmentioning
confidence: 99%
“…To ensure that the test antenna full recovered from a stimulus, there was a 60 s interval between tests. The test of each pheromone was from a low concentration to a high concentration (Zhang et al, 2010). A hexane-only control and standard solution (1-hexanol at 1 μg/μL in hexane) was presented before and after each test pheromone.…”
Section: Introductionmentioning
confidence: 99%